Nectary structure of Ornithidium sophronitis Rchb.F. (Orchidaceae: Maxillariinae) - Małgorzata Stpiczyńska; Kevin L. Davis; Alan Gregg (Acta Agrobotanica, 2012)
Most orchids do not produce floral food-rewards. Instead, they attract pollinators by mimicry or deceit. When present, the most common floral food-reward is nectar. To date, nectary structure has been described for only two species of Maxillaria sensu lato, namely Maxillariella anceps and Ornithidium coccineum (formerly Maxillaria anceps and M. coccinea, respectively). Here, we describe that of a third species, Ornithidium sophronitis (formerly Maxillaria sophronitis). This species possesses floral characters concomitant with ornithophily. A 'faucet and sink' arrangement is present, with nectar secreted by a protuberance on the ventral surface of the column, collecting between column and tepal bases. The nectary of O. sophronitis shares many features with that of O. coccineum. It has a single-layered epidermis and 3- 5 layers of small, subepidermal, collenchymatous, secretory cells. Beneath these occur 2-3 layers of larger, subsecretory, parenchymatous cells supplied by phloem. Nectary cell vacuoles contain osmiophilic material and proteinaceous intravacuolar bodies. Moreover, distension of the nectary cuticle occurs as nectar accumulates between it and the secretory epidermis. Subsecretory cells, however, have thinner walls and contain flocculent, intravacuolar precipitates that may be related to the presence of flavonoids. Since the floral and nectary structure of O. sophronitis is very similar to that of closely related Ornithidium coccineum, it may have evolved in like manner in response to similar pollinator pressures.